2007
DOI: 10.1080/13698570701612527
|View full text |Cite
|
Sign up to set email alerts
|

Coronary heart disease and the management of risk: Patient perspectives of outcomes associated with the clinical implementation of the National Service Framework targets

Abstract: This paper explores developments in the risk management of coronary heart disease (CHD) that have followed the implementation of the Coronary Heart Disease National Service Framework (NSF) guidelines from the patient's perspective. The CHD NSF introduced in 2000 set national threshold targets for blood pressure and cholesterol levels for primary care managed patients, it also laid down guidelines for the clinical management of those patients deemed to be at 'high cardiac risk.' Additionally, following the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…The case of statins is used here to problematise that tension, highlighting the articulation between critiques of ‘dependency’ on doctors and pills (Crinson et al . ) and the growing valorisation of the autonomous, self‐determining individual characterised by Crawford () as a ‘bourgeois ideal’. This study suggests that those offered statins negotiate a complex tangle of conflicting norms which is perhaps too seldom considered by those who advise or study them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The case of statins is used here to problematise that tension, highlighting the articulation between critiques of ‘dependency’ on doctors and pills (Crinson et al . ) and the growing valorisation of the autonomous, self‐determining individual characterised by Crawford () as a ‘bourgeois ideal’. This study suggests that those offered statins negotiate a complex tangle of conflicting norms which is perhaps too seldom considered by those who advise or study them.…”
Section: Discussionmentioning
confidence: 99%
“…Within the social science literature, this trope is sometimes implicitly in tension with a broader anti-medicalisation discourse that highlights the medicalising effect of individual responsibilisation for health and identifies healthism as 'a form of medicalisation' (Crawford 1980: 381). The case of statins is used here to problematise that tension, highlighting the articulation between critiques of 'dependency' on doctors and pills (Crinson et al 2007) and the growing valorisation of the autonomous, self-determining individual characterised by Crawford (1994) as a 'bourgeois ideal'. This study suggests that those offered statins negotiate a complex tangle of conflicting norms which is perhaps too seldom considered by those who advise or study them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no studies on how real users who have undergone CHD risk assessment and prevention experience this contradiction. A focus‐group study found that patients were frustrated with the restriction of heart disease prevention to the clinical monitoring of cholesterol levels and manipulating them with medications (Crinson et al 2007). Risk assessment technologies may play a greater role in influencing individuals’ experience of CHD risk, because it is considered imperceptible (Angus et al 2005).…”
Section: Introductionmentioning
confidence: 99%